PENGELOLAAN SARANA DAN PRASARANA DI SMP MUHAMMADIYAH WALATTASI KABUPATEN SOPPENG - A.Tryfamanda; Wahira; Ahmad Restani Syukron Thayyib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the management of educational facilities and infrastructure (sarana and prasarana) at SMP Muhammadiyah Walattasi, Soppeng Regency, focusing on procurement and maintenance processes and the supporting and inhibiting factors. This research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation involving the school principal, teachers, and administrative staff. The results indicate that facility procurement has been carried out systematically through needs analysis, priority determination, and budget planning integrated into the School Activity and Budget Plan (RKAS). Maintenance activities are conducted routinely through daily and weekly cleaning, periodic inspection, and minor repairs. Supporting factors include effective leadership by the principal, collaborative school community, adequate planning, and funding from BOSP grants and Muhammadiyah organizational support. Inhibiting factors include budget limitations, aging facilities, lack of technology infrastructure, insufficient user awareness, and the absence of dedicated facility management personnel. The study concludes that despite these constraints, the school manages its facilities functionally to support learning activities, though improvements are needed in equalization of resources, technology integration, and the appointment of specialist facility management staff.